Synthesis of Poly(styrene-acrylates-acrylic acid) Microspheres and Their Chemical Composition towards Colloidal Crystal Films - Luis A. Ríos-Osuna; Angel Licea-Claverie; F. Paraguay-Delgado; Norma A. Cortez-Lemus (International Journal of Polymer Science)
In this paper, polystyrene colloidal microspheres have been prepared using hexyl acrylate (HA), ethylhexyl acrylate (EHA), isooctyl acrylate (IOA), butyl acrylate (BA), or isobutyl acrylate (IBA) as comonomers. Microspheres with diameters from 212 to 332 nm and with a polystyrene content of 65–78% were prepared. The particles prepared in this work do not present the typical core-shell structure; as a consequence, DSC analysis showed that the microspheres exhibited only one Tg. TEM images show that the particles with comonomer content below ~30% were spherical and regular. Microspheres containing comonomer between 21 to 25% produced the less brittle films showing very iridescent colors. The films prepared from microspheres containing hexyl, ethylhexyl, and isooctyl acrylate as comonomers are firmly attached to the substrate due to their adhesive properties. The large decrease of the fragility observed in these films makes them much more attractive materials in sensing applications.